MCSE training guide : SQL server 6.5 design and implementation - Baird, Sean.; Besch, David; Darveau, Denis; Smith, Wayne; Townsend, Deanna (Indianapolis, IN : New Riders Pub., 1997)
Information needed to pass this exam is presented in this book. Utilizing the knowledge of MCSEs and MCTs, it contains insider tips, notes, and strategies readers need to become an MCSE. The book contains test questions, lists, tables, notes, tips and tricks.
Includes index.
Keywords: Electronic data processing personnel -- Certification; Microsoft software -- Examinations -- Study guides; SQL server